2013
DOI: 10.1111/cbdd.12116
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antidepressant Evaluation and Docking Studies of Long‐Chain Alkylnitroquipazines as Serotonin Transporter Inhibitors

Abstract: Twelve alkyl analogues (1 - 12) of the high-affinity serotonin transporter (SERT) inhibitor 6-nitroquipazine (6-NQ) were synthesised and studied using in vitro radioligand competition binding assays to determine their binding affinity (Ki). The putative antidepressant activity of five of the binders with the highest SERT binding affinities was studied by the forced swim and locomotor activity mouse tests. The three dimensional (3D) structures of 8 and 9 were determined using NOE NMR technique. Flexible docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Thus, in that earlier study, we reported that the main interaction underlying the affinity of these compounds at the SERT was a coulombic interaction established by a piperazine nitrogen with Asp400, a residue located a few angstroms closer to the extracellular domain of the SERT as compared with Glu493. Noteworthy, diverse studies (see for example ) have shown that both Asp400 and/or Glu493 are critical for the binding of different arylpiperazine derivatives. In our view, an alternating interaction involving both residues might be the main molecular determinant explaining the affinity of these and other SERT ligands.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in that earlier study, we reported that the main interaction underlying the affinity of these compounds at the SERT was a coulombic interaction established by a piperazine nitrogen with Asp400, a residue located a few angstroms closer to the extracellular domain of the SERT as compared with Glu493. Noteworthy, diverse studies (see for example ) have shown that both Asp400 and/or Glu493 are critical for the binding of different arylpiperazine derivatives. In our view, an alternating interaction involving both residues might be the main molecular determinant explaining the affinity of these and other SERT ligands.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, this study shows for the first time a selenium compound binding affinity with serotonin transporters and the serotonin receptors: 5HT 1a, 5HT 2a and 5HT 3 which might be useful to unravel the mechanism of action antidepressant-like effect exerted by several selenium compounds, as cited previously . Moreover, similar studies already demonstrated the antidepressant-like effect using this docking methodology in mice submitted to FST [ 69 71 ].…”
Section: Resultsmentioning
confidence: 76%
“…New SERT inhibitors, compounds KW117 ( 6 ), AZ05 ( 7 ), AZ07 ( 8 ), AB5A ( 9 ), AB9 ( 10 ), AB21 ( 11 ) and AB22 ( 12 ), possessed a nanomolar affinity for SERT ( Table 1 ). Compounds KW117 ( 6 ), AZ05 ( 7 ) and AZ07 ( 8 ) exhibited moderate antidepressant activity in the in vivo Porsolt forced swim test [ 6 ]. It appeared that almost all of the examined compounds (besides 5-HT 1A receptor agonist 8-OH-DPAT, SSRI fluvoxamine against SH-SY5Y and AB9 against both tumor lines) exhibited moderate to high cytotoxic activity at the micromolar level against neuroblastoma and prostate cancer cells ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…KW117 (6-nitro-2-(4-octylpiperazin-1-yl)quinoline hydrochloride) ( 6 ), AZ05 (6-nitro-2-(4-nonylpiperazin-1-yl)quinolone hydrochloride) ( 7 ), and AZ07 (6-nitro-2-(4-undecylpiperazin-1-yl)quinoline hydrochloride) ( 8 ) were obtained as described in Gabrielsen et al [ 6 ]. New compounds: AB5A (2-[4-(4-fluorobenzyl)piperazin-1-yl]-6-nitroquinoline hydrochloride) ( 9 ), AB9 (6-nitro-2-[4-(2-phenylethyl)-piperazin-1-yl]-6-nitroquinoline hydrochloride) ( 10 ), AB21 (2-[4-(cyclohexylmethyl)piperazin-1-yl]-6-nitroquinoline hydrochloride) ( 11 ), and AB22 (2-[4-(cyclobutylmethyl)piperazin-1-yl]-6-nitroquinoline hydrochloride) ( 12 ) were synthesized as described below in Section 6 —Experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation